KONTRIBUSI PENGUASAAN KOMPETENSI GURU MELALUI PLK TERHADAP MINAT MENJADI GURU BAGI MAHASISWA PROGRAM STUDI PENDIDIKAN TEKNIK BANGUNAN FT-UNP - 286-293 , Denni Saputra (CIVED, 2014)
ABSTRACT   The aim of this research to determine the contribution of mastery of the competency of teachers with PLK (Praktek Lapangan Kependidikan) the interest to be a teacher  by students of Pendidikan Teknik Bangunan of Civil Enggineering FT-UNP the class of 2009.This research method descriptive study conducted. The subjects are students of Pendidikan Teknik Bangunan of Civil Enggineering FT-UNP the class of 2009, that have implemented PLK.  The data was collected using a questionnaire and documentation. The technique of data analysis was performed by using descriptive correlational analysis. The results of this research indicate that students of Pendidikan Teknik Bangunan of Civil Enggineering FT-UNP the class of 2009,  within the competence of the teacher as PLK (Praktek Lapangan Kependidikan) mastery by 32 respondents (96.96%) including the excellent category and 1 respondent (3.03%) including the good categories. Interest of students to be included in the category of enough teacher which is 70%. While mastery of the competency of teachers have contributed to the interest in becoming a teacher of 33.87%. The research results, we can conclude the better mastery of the competency of teachers, the greater the contribution to the interest in becom a teacher. Keywords: Teacher Competencies, Interests Being a Teacher